Rangelands and pastoralism of the Middle-East and North Africa, from reality to dream - Naghizadeh, Nadia; Badripour, Hossein; Louhaichi, Mounir; Gamoun, Mouldi; Niamir-Fuller, Maryam (Kenya Agricultural and Livestock Research Organization, 2022)
The Middle East and North Africa (MENA) is a vast area covering 20 countries from western Asia to North Africa, with nearly 9,000,000 Km2 and 303 million hectares of total rangelands. Rangelands play an essential role in supporting people’s livelihoods and food security. Mobile pastoralism is the most viable and resilient form of production and land use in the fragile drylands of MENA. However, the region’s governments have considered nomadic pastoralism backwards mainly because it was challenging to deliver mobile services. They designed various policies that were not in harmony with pastoralists’ customary rules and norms and severely weakened their mutual aid associations and governance systems for natural resources management. Nowadays, pastoralists’ rangelands and customary territories are shrinking, fragmenting, and degrading due to various reasons, but mainly the expansion of agricultural or industrial needs. Based on pastoralists and rangelands’ socio-ecological values, the world needs to apply the evidence-based experiences and Indigenous knowledge of pastoralists in preventing rangeland degradation. It is urgent to start a new paradigm shift for an inclusive interaction, establishing pro-poor livestock policies. These policies would address the barriers and bottlenecks faced by pastoral and agro-pastoral communities and secure land tenure at community and landscape levels through multi-stakeholder dialogue, including during the International Year of Rangelands and Pastoralists (IYRP). It is time to call for respect of customary governance systems of pastoralists, recognition of their territories as Indigenous and Community Conserved Areas (ICCA3s—territories of life) under various and norms in the region like Qoroq, Hima, Agdal, and any other form of local conservation to prevent fragmentation of pastoralists territories and rangelands degradation leading to desertification.